Setting Incentives: Temporary Performance Premiums Versus Promotion Tournaments - Volker Meier (Center for Economic Studies and ifo Institute (CESifo), 2001)
Two alternative relative compensation schemes are compared with respect to total output that can be generated at a given sum of salaries. While the promotion regime guarantees that any salary increase is permanent, the premium system allows a reduction in the income of an agent to the base salary after one period. It is shown that the optimum promotion tournament system induces a higher total output than the optimum premium system. This result occurs because a promotion regime allows distortion in a contest in favor of winners of previous contests.
Keywords: 330; Tournament; relative compensation; internal labor markets